(3eMGVQGJ aj GdGbJUGO GdLRFj (B/s - (3GMeO OGhO, GHQGgjes ((3GdLRGFQ(B: s (3GdeDSSI GdhWfjI(B, s, 1984)
(3JLO aj gPG GdcJGH (B1- (3fXQjI GdeSJgdc (B- (3GdefaYI (B2- (3fXQjI GdeSJgdc (B- (3efMfjGJ GdShGA (B3 (3CKQ GJdONd CKQ GdGMdGd hCKQ GdKef (B4- (3GdWdH (B-5- (3GdYQV (B-6- (3GdKef (B-7- (3GdCKeGf aj GdMjGI GdYedjI (B-8- (3GdGfJGL (B-9- (3GdJcGdja (B-10 (3GdGjQGOGJ (B-11- (3gjcd GdShb hJhGRf GdeDSSI (B- (3GdefGaSI GdHMKjI (B12- (3gjcd GdShb hJhGRf GdeDSSI (B: (3GdGMJcGQ GdHMK (B13- (3gjcd GdShb hJhGRf GdeDSSI GdefGaSI GdGMJcGQjI (B14- (3gjcd GdShb hJhGRf GdeDSSI GdGMJcGQ GdeJYOO (B-(3GdeQGLYs
Keywords: (3GbJUGO LRFjs